An overview of the development of the hybrid method for seismic vulnerability assessment of buildings. Issue 12 (1st December 2016) - Kappos, Andreas J.
Abstract: The paper presents in a chronological and systematic way the development of the hybrid method for seismic vulnerability assessment of structures, which combines the use of empirical databases of earthquake damage with the results of nonlinear analysis of representative structural models. The key concepts and milestones in the development of the method are identified, and selected examples of its application are summarised. The first part of the paper focuses on the derivation of hybrid damage probability matrices and the second one with the derivation of fragility curves for reinforced concrete and masonry buildings. Finally, some general conclusions are drawn and directions of future research on the hybrid approach are suggested.